Online Learning Platform as MALL Application Due to Covid-19 Pandemic - Lilik Yuliawati (English Teaching Journal : A Journal of English Literature, Language and Education, 2022)
COVID-19 pandemic forces the change of education system in Indonesia from conventional to online because of the face-to-face learning prohibition from the Indonesian government. In such situation, Mobile Assisted Language Learning (MALL) is needed, and some online learning platforms are provided by higher education institutions, one of which is MyBest. This research aimed to determine students’ perception towards MyBest as online learning platform. Mixed Method using quantitative and qualitative data was applied in this research. Data were collected by giving questionnaire and doing interview with the students of Bina Sarana Informatika University as respondents. The research results showed that most of the students gave positive opinion about this platform because it could help them learn the lesson better. Yet, they also faced some problems in using it such as low internet connection and uncomfortable eyes when reading a long text on screen.